Comunicação e consumo transmídia : estratégias discursivas interativas da Nike para a celebração do consumo - Reis, Gustavo Tadeu Testa (2017)
How global brands build relevant communication in a contemporary society transmissia It is on the basis of this questioning that this research project promotes dialogue between the production and adaptability of advertising narratives in digital communication environments, taking into account the speed and fluidity with which they expand and the possibilities of transposition of the medium of origin, creating a web of new messages and resignifications. The search is based on the articulation of three thematic axes: communication through analysis of flows digital images that bring emitter and receiver into story building; consumer practices with the reflection on the cultural and social relations of goods, their representations as they delimit a path through which individuals project and see themselves, and as the current communicational model between product and producer in the emission of messages and in the interpretation of the senses, creating a symbolic network that composes the construction of the self and subjectivity through appropriations; and the cyberculture that will serve as a map to navigate among the resonant cultural mutations of devices information and communication. The focus of the survey is on Nike Inc., especially the "Come Together", which, via online platforms, allows the creation and promotion of personalized physical activities in public places in the main cities of Brazil. The advertising pieces images and textual content produced by the users and published on the networks on the events will compose the empirical corpus of the study, which will be analyzed through the netnographic observation on the own platforms of the brand and analysis of French line discourse in what concerns storytelling as a message structuring element. The present study proposes reflection on the participatory model of a transmedia advertising communication and the possibility, via media subsystems, to promote the sharing of consumer experiences.